(3GdXGgQI GdELQGejI (B:s ((3OQGSI JMdjdjI JCUjdjI ebGQfI dCSHGH GdLQjeI(B) /s - (3GdeQGZj, CMeO YHO GddGgs ((3GdLjRI, eUQ (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd cJGH (B((3GdXGgQI GdELQGejI (B: (3OQGSI JMdjdjI JCUjdjI ebGQfI dCSHGH GdLQjeI(B) (3hGdPj bGe HJCdjag (B((3CMeO YHO GddGg GdeQGZj(B) (3aj MhGdj (B(444) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3Yde GdELQGe(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GSJgdGd, GdebOeI, GdbSe GdChd (B: (3GdeHGOF GdChdjI aj Yde GdELQGe, GdbSe GdKGfj (B: (3JaSjQ GdXGgQI GdELQGejI, GdbSe GdKGdK (B: (3GdYhGed GdELQGejI GdOGNdjI, GdbSe GdQGHY (B: (3GdYhGed GdELQGejI GdNGQLjI(B.s
(3GdeMJhjGJ (B: (3ebOeI(B-(3GdbSe GdChd (B: (3GdeHGOjA GdChdjI aj Yde GdELQGe, GdHGH GdChd (B: (3eGgjI Yde GdELQGe (B...-(3GdbSe GdKGfj (B: (3JaSjQ GdXGgQI GdELQGejI, GdHGH GdChd (B: (3GdeOGQS GdJchjfjI Gh GdHjhdhLjI aj JaSjQ GdXGgQI GdELQGejI (B...-(3GdbSe GdKGdK (B: (3GdYhGed GdELQGejI GdOGNdjI, GdHGH GdChd (B: (3GdYhGed GdOGNdjI GdCUdjI (B...-(3GdbSe GdQGHY (B: (3GdYhGed GdELQGejI GdNGQLjI, GdHGH GdChd (B: (3GdHjFI GdELQGejI hGdXGgQI GdELQGejI (B... (3hehVhYGJ CNQi(B.s
(3HHdjhLQGajI (B: (3UaMI (B405-435.s
Keywords: (3Yde GdELQGes; (3GdLQjeI hGdeLQehfs; (3Yde GdELQGes; (3GdLQjeI hGdeLQehfs -- (3LhGfH GLJeGYjIs; (3bGfhf GdYbhHGJs; (3GdLQjeI hGdeLQehfs -- (3LhGfH SjGSjIs; (3EOeGf GdeNOQGJs -- (3LhGfH GLJeGYjIs; (3GdLQjeI hGdeLQehfs -- (3LhGfH GbJUGOjIs; (3Yde GdfaS GdGLJeGYjs; (3Yde GdfaS GdLfGFj s; (3GdCfKQhHhdhLjG GdLfGFjIs; (3GdeSM GdGLJeGYjs; (3GdSdhc GdELQGejs; (3GdXGgQI GdELQGejIs